2018
DOI: 10.4014/jmb.1804.04017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Headspace Volatolome, Primary Metabolites, and Aroma Characteristics of Koji Fermented with Bacillus amyloliquefaciens and Aspergillus oryzae

Abstract: Production of good Koji primarily depends upon the selection of substrate materials and fermentative microflora, which together influence the characteristic flavor and aroma. Herein, we performed comparative metabolomic analyses of volatile organic compounds (VOCs) and primary metabolites for Koji samples fermented individually with Bacillus amyloliquefaciens and Aspergillus oryzae. The VOCs and primary metabolites were analyzed using headspace solid phase microextraction (HS-SPME) followed by gas chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The fold changes of volatile compounds, which were calculated compared to the control (RICE), were classified by three main metabolic pathways, including carbohydrate, amino acid, and fatty acid metabolism (Table S1). Heatmaps were clustered by defined pathways provided from kyoto encyclopedia of genes and genomes (KEGG) pathways and previous studies [15,16,17]. The tendency to increase or decrease compared to the control was shown in five stages (blue; positive, red; negative, and gray; not detected), while the formation of volatile compounds which were not detected in the control but were newly produced during fermentation, were marked separately (purple; newly detected, white; not detected).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fold changes of volatile compounds, which were calculated compared to the control (RICE), were classified by three main metabolic pathways, including carbohydrate, amino acid, and fatty acid metabolism (Table S1). Heatmaps were clustered by defined pathways provided from kyoto encyclopedia of genes and genomes (KEGG) pathways and previous studies [15,16,17]. The tendency to increase or decrease compared to the control was shown in five stages (blue; positive, red; negative, and gray; not detected), while the formation of volatile compounds which were not detected in the control but were newly produced during fermentation, were marked separately (purple; newly detected, white; not detected).…”
Section: Resultsmentioning
confidence: 99%
“…For example, S. cerevisiae is well known as a higher producer of ethanol and fusel alcohols. In addition, 2-methylbutanal and 3-methylbutanal are major fermentative compounds, induced from fungi, such as A. oryzae [16], while lactic acid bacteria are superior for generating organic acids, including acetic acid, and butanediol fermentation [37]. However, we were able to investigate the characteristic features of volatile compound profiles in rice fermentation according to each microbe.…”
Section: Discussionmentioning
confidence: 99%
“…Seo et al . (2018a) and Seo et al . (2018b) studied koji produced from soybean and a combination of cereals.…”
Section: Gc‐ms‐based Metabolomics Of Clffsmentioning
confidence: 95%
“…Using a combination of SPME‐GC‐MS and GC‐TOF‐MS‐based metabolomics, Seo et al . (2018a) compared the volatile organic compounds and primary metabolites in koji samples fermented individually with Bacillus amyloliquefaciens and Aspergillus oryzae . Through these integrated approaches, the authors concluded that the volatile profile of koji is largely determined by the inocula choice, which modifies the primary metabolites in koji substrates, subsequently influencing its aroma characteristics.…”
Section: Gc‐ms‐based Metabolomics Of Clffsmentioning
confidence: 99%
“…Numerous studies focused on Bacillus and Aspergillus species as the main microorganisms in fermented soybean products and found volatile organic acids, alcohols, and esters were predominant and their levels varied with the associated microorganisms during fermentation process (Kum et al, 2015;Leejeerajumnean et al, 2001;Seo et al, 2018). Recently, Seo et al (2018) reported the differences of volatile profiles between koji fermented by B. amyloliquefaciens and A. oryzae.…”
Section: Differences Of Volatile Compositions Between Two Bs Samplesmentioning
confidence: 99%